Decavanadate induces mitochondrial membrane depolarization and inhibits oxygen consumption - Soares, Sandra S. (2012)
Decavanadate induced rat liver mitochondrial depolarization at very low concentrations, half-depolarization with 39 nM decavanadate, while it was needed a 130-fold higher concentration of monomeric vanadate (5 lM) to induce the same effect. Decavanadate also inhibits mitochondrial repolarization induced by reduced glutathione in vitro, with an inhibition constant of 1 lM, whereas no effect was observed up to 100 lM of monomeric vanadate. The oxygen consumption by mitochondria is also inhibited by lower decavanadate than monomeric vanadate concentrations, i.e. 50% inhibition is attained with 99 nM decavanadate and 10 lM monomeric vanadate. Thus, decavanadate is stronger as mitochondrial depolarization agent than as inhibitor of mitochondrial oxygen consumption. Up to 5 lM, decavanadate does not alter mitochondrial NADH levels nor inhibit neither FOF1-ATPase nor cytochrome c oxidase activity, but it induces changes in the redox steady-state of mitochondrial b-type cytochromes (complex III). NMR spectra showed that decameric vanadate is the predominant vanadate species in decavanadate solutions. It is concluded that decavanadate is much more potent mitochondrial depolarization agent and a more potent inhibitor of mitochondrial oxygen consumption than monomeric vanadate, pointing out the importance to take into account the contribution of higher oligomeric species of vanadium for the biological effects of vanadate solutions.